Implementation of an e-learning prototype for studying 21st-century learning models for prospective biology teachers - Malahayati, Eva; Putriani, Ida; Sofiyana, Marinda Sari (Biosfer: Jurnal Pendidikan Biologi, 2025)
The need to master 21st century skills demand preservice teachers to have pedagogical competencies that are adaptive to change, especially in terms of implementing 21st century learning models and integrating technology into learning. One solution to meet the demands of preservice teachers is e-learning, a flexible, adaptive and interactive learning that allows users to access content anywhere, following structured stages. The success of e-learning depends on the effectiveness of implementing an approach such as DARP (Discuss, Archive, Reflect, and Prepare). This approach ensures that the e-learning platform is interactive, reflective and evaluative. The aim of this research is to examine the response of users of e-learning prototypes of 21st century learning models designed with a reflective and interactive approach. This initial prototype was developed to meet user needs and align with the intended goals, using a usability questionnaire for evaluation. The method used in this research is SDLC (System Development Life Cycle) which consists of five stages, namely planning, analysis, design, implementation and testing. This research involved 30 students and 2 lecturers, and the usability of the e-learning platform was assessed using the USE Questionnaire. The development of this prototype received positive feedback from both students and lecturers, this shows that DARP-based e-learning can be further developed as a learning platform to support improving the pedagogical competence of 21st century preservice teacher.